The relationship between management and tourism, based on the experience of the visitor - Llontop Diez, Claudia Edith (2017)
This research describes the tourism environment and its relationship in a connected world according to the economy of the experience theory by Pine and Gilmore. It proposes the need to integrate management as a driving force of the tourism experience from the understanding of the human experience and the tourist attitude in the designs or development plans of tourist products, orienting the study to the development of a model that acts like a vehicle capable of granting the visitor a tourist experience.